Analisis Perbedaan Pembelajaran Bahasa Inggris Maritim Melalui Kelas Dan Simulator - prayitno, edy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Akademi Maritim Cirebon, 2023)
English is also not only set as the main language in a country but in every work activity it is too often used, English is also set as a language that must be known and owned by a seafarer, including Indonesian seafarers who work on Indonesian shipping. The term Marine English used in the maritime sphere appears, Maritime English is one of the ESP (English For Special Purposes) which requires experience and professional knowledge at a certain level to be able to understand it comprehensively, The results of this study are about the analysis of differences in maritime English learning through simulators and class, this study uses a non-parametric comparative method with technical data analysis using the Mann Witney test with a total of 162 respondents consisting of all cadets / I majoring in nautical force 54 with test results in the Mann Whitney test with the Asympt sig theory test (2 tailed) of 0.000 is smaller than 0.05, therefore it can be concluded that Ha is accepted (there is a significant difference between learning maritime English through simulators and classes at the Bumi Akpelni Polytechnic Semarang) and the results of the practical test in the Mann Whitney test and the Asymp practical test. Sig (2 tailed) of 0.08, greater than 0.05, it can be concluded that Ha is rejected (There is no significant difference between learning maritime English through simulators and classes at the Bumi Akpelni Polytechnic Semarang)